Regenerative Medicine 2020
DOI: 10.5772/intechopen.90543
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Activation, and Mechanism of Action of Platelet-Rich Plasma and Its Applications for Joint Repair

Abstract: Platelet-Rich Plasma (PRP) is a biologic therapy that uses the patient's own blood to obtain products with a higher platelet concentration than in blood. This technology provides a controlled drug delivery system of growth factors suitable for regenerative medicine. The biological effects of PRP mimic and influence biological processes such as inflammation, analgesia, and cell stimulation, providing this therapy with promising therapeutic potential. All these processes participate in maintenance, correct funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…PRP contains high levels of biomolecules that participate in different biological processes that favouring cellular repair. 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRP contains high levels of biomolecules that participate in different biological processes that favouring cellular repair. 7 …”
Section: Introductionmentioning
confidence: 99%
“…PRP contains high levels of biomolecules that participate in different biological processes that favouring cellular repair. 7 An increasing number of randomized clinical trials (RCTs) are being conducted to draw firm conclusions regarding the efficacy and safety of PRP, with promising results. 8 Although RCTs are the cornerstone of evidence-based medicine, their use for the study of PRP has certain limitations.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins were found to promote the formation of extracellular matrix, cellular replication, angiogenesis, cell proliferation and differentiation [ 62 ]. Upon intra-articular injection of non-activated PRP into a defect, PRP can be activated by contact with local tissue factor [ 63 , 64 ].…”
Section: Platelet-rich Plasmamentioning
confidence: 99%
“…Despite promising results and the increasing volume of research on PRP, there is still a need to better understand the mechanisms of action through which it carries out its work. However, it seems to be well established that many of the actions of PRP occur through the modulation of cellular activity [ 6 ]. Thus, numerous studies have shown that PRP stimulates cell proliferation, which is a key process in the treatment of pathologies that require cellular restoration of tissue, such as degenerative lesions and wound-healing processes.…”
Section: Introductionmentioning
confidence: 99%